THE CRISIS OF IDENTITY IN POSTCOLONIAL LITERATURE: MALAYSIAN ENGLISH LITERATURE AND BRITISH LITERATURE - Alsalim, Hafudh F.; Sanif, Sazuliana (International Journal of Psychosocial Rehabilitation, 2020)
The period of time which followed World War II was the period of an act to ask for decolonisation and freedom of nations which were under the rule of the colonial power to move forward in the direction of reforming social and individual identities. Therefore, the question of identity became one of the most important issues in postcolonial time and literature for its crisis that exists in all the postcolonial societies. The crisis of identity floated on the surface as a result of the conditions of the postcolonial period and the difficult circumstances that the newly freed nations and countries faced in their seeking and formation of self-identity. The purpose of the study is to explore the loss of identity that the individual encounters during the process of searching for an identity during the colonial and postcolonial time, focusing on Malaysian English literature and British literature to show the difference between the two in this concern. In this qualitative study, the researcher followed the postcolonial theory using textual and content analysis to analyse two postcolonial novels (Emily Bronte’s Wuthering Heights and K.S. Maniam’s The Return) to show the effects of colonialism on colonised communities regarding the matter of identity loss. Thus, the matter of identity is examined through the coloniser’s and the colonised’s views to show the difference between the two. The main finding is that the colonised is silenced in the coloniser’s text as in (Emily Bronte’s Wuthering Heights) while he is voiced in the colonised’s text as in (K. S. Maniam’s The Return). The study sheds light on one of the main issues which is the way how the white and the nonwhite (the coloniser and the colonised) portrayed the character of the colonised in their texts.